2008
DOI: 10.1074/jbc.m804257200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Site on PAI-1 That Binds to Vitronectin Outside of the Somatomedin B Domain

Abstract: Vitronectin and plasminogen activator inhibitor-1 (PAI-1) are proteins that interact in the circulatory system and pericellular region to regulate fibrinolysis, cell adhesion, and migration. The interactions between the two proteins have been attributed primarily to binding of the somatomedin B (SMB) domain, which comprises the N-terminal 44 residues of vitronectin, to the flexible joint region of PAI-1, including residues Arg-103, Met-112, and Gln-125 of PAI-1. A strategy for deletion mutagenesis that removes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 51 publications
6
58
0
Order By: Relevance
“…9). There is also evidence that VN has additional binding interactions with active PAI-1 outside the somatomedin domain B involving residues in ␣-hD (Lys-69, Arg-76, Tyr-79, and Lys-80) and ␣-hE (Arg-115 and Arg-118) (26,27). Some of these residues are the same as those interacting with AZ3976 in the present structure, i.e.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…9). There is also evidence that VN has additional binding interactions with active PAI-1 outside the somatomedin domain B involving residues in ␣-hD (Lys-69, Arg-76, Tyr-79, and Lys-80) and ␣-hE (Arg-115 and Arg-118) (26,27). Some of these residues are the same as those interacting with AZ3976 in the present structure, i.e.…”
Section: Discussionsupporting
confidence: 48%
“…Still, PAI-1 ex vivo in blood has a half-life of only ϳ1 h at 37°C (24). It has been found that PAI-1 binds to the N-terminal ϳ50-amino acid somatomedin B domain of VN (25)(26)(27). X-ray evidence (23) suggests that binding to this domain induces conformational changes in PAI-1 which, in addition to steric effects, may contribute to its improved stability.…”
mentioning
confidence: 99%
“…DENV NS1-VN interaction is increased by PAI-1 and inhibited by plasminogen. VN can bind several molecules, such as heparin, PAI-1, HPX, and PLG, and these interactions occur at distinct sites in the VN molecule (23)(24)(25)(26)(27). Therefore, to identify the putative binding sites of NS1 on the VN molecule, competitive ELISAs were performed in which VN ligands were used as competitors (28).…”
Section: Identification Of Vn As An Ns1-interacting Partnermentioning
confidence: 99%
“…Plasminogen activator inhibitor 1 (PAI-1) is an effective inhibitor of plasminogen activators, particularly urokinase-plasminogen activator (uPA) and tissue-type plasminogen activator, and binds to the LDL receptor (LRP) and vitronectin (25,33). Although increased levels of PAI-1 and inhibition of plasmin generation are found in the lungs and circulation of critically ill patients with sepsis or ALI (28,40), recent studies have also shown that PAI-1 can affect a broad range of cellular functions independent of its effects on coagulation, including cell adhesion, proliferation, migration, and viability (6,21,36).…”
mentioning
confidence: 99%